Uncertain Democracy : U.S. Foreign Policy and Georgia's Rose Revolution - Mitchell, Lincoln Abraham (Book collections on Project MUSE., 2009)
Lincoln Mitchell tracks the course of events leading up to the recent revolution in the former Soviet republic of Georgia, analyzes the contributing factors, and explores the role of the United States both in contributing to the revolution and in Georgia's failure to live up to its democratic promise.